Carbon footprint of private dental laboratories in Egypt: A cross-sectional study - Amira H. Elwan; Ahmed Mahmoud Fouda (BDJ Open)
Abstract Background Climate change poses a serious threat to the planet, mainly driven by greenhouse gas (GHG) emissions. Dental laboratories contribute to GHG emissions through staff travel, waste, energy and water consumption, and procurement. Carbon footprinting is the process of quantifying the direct and indirect GHG emissions associated with a service. This study aimed to assess the Carbon Footprint (CFP) of private dental laboratories in Egypt. Materials and methods Data were collected from private dental laboratories in Cairo, Alexandria, and Elbeheira, Egypt in August 2024 through interview questionnaires. A CFP calculator was used to estimate carbon emissions from staff travel, waste, energy and water consumption, and procurement. The data of all laboratories was summed and divided to determine the average CFP per laboratory and per prothesis/appliance, both with and without the depreciation of dental equipment. Results Data from 21 dental laboratories were collected. An average private dental laboratory in Egypt worked 309 days with a staff of around 7 persons and makes around 7119 prostheses/appliance per year. The CFP of dental laboratories was around 20,820 kg CO2e, equal to 2.9 kg CO2e per prosthesis/appliance. The largest contributor to the CFP was staff travel (43.6%), followed by procurement (27.8%), energy consumption (25%), waste (3.3%), and water consumption (0.1%). After including the depreciation of dental equipment, the CFP increased by 7.7%. Conclusion Private dental laboratories in Egypt produce a significant amount of carbon emissions. Staff travel was the major contributor to the carbon emission because each laboratory hired several couriers to deliver the prostheses/appliances and impressions. The CFP of electricity consumption was significant, likely because the air conditioning ran throughout the year to cool the machines down. Future studies are needed to develop customized country-specific CFP calculators to accurately measure the carbon emissions of dental laboratories in various settings. Preventing oral diseases, educating technicians on sustainable dental practices, optimizing public transportation, using bulk delivery services, shifting to renewable energy, and adopting circular economy are essential to mitigate the carbon emissions of dental laboratories.